Arbejdernes Fællesbagerier: Kooperativ succes og modgang 1884-1980 - Sørensen, Kasper (Arbejderhistorie - tidsskrift for historie, kultur og politik, 2013)
Kasper Sørensen: Cooperative Bakeries in Denmark – success and failure of the workers’ cooperative business model 1884-1980, Arbejderhistorie 1/2013, pp. 1-xx. The co-operative bakeries were among the earliest and, for a period, most successful of the businesses in the Danish workers’ Cooperative movement. These were founded and owned by the consumers, often on the initiative of the local labour organisations, with the purpose of securing the supply of cheap and good bread, rather than the traditional business objective of maximising profit. For a while, mainly in the period before the Second World War, these bakeries successfully achieved both business progress and the fulfilling of their objective of influencing bread prices. This success was most likely only made possible by the wide-spread support of the consumers. The identity of the co-operative bakeries as businesses integrated in the working-class cultural network of the local community made the consumers, which were part of that cultural network, prefer the bread of “their own” bakeries rather than that of the private bakeries. However, since the 1950’s the workers’ co-operative bakeries faced increas-ing economic difficulties due to a failure to carry through the necessary structural ratio-nalization. By the mid-1980’s almost all of them had been forced to close down or turn over their businesses to other companies. Thus the history of the workers’ co-operative bake-ries shows both the success and failure of the workers co-operative business model.